Need Analysis of Basic Chemistry Practicum Based on Computation - Dona Mustika; Hasby Hasby; Ulil Azmi (Jurnal Penelitian Pendidikan IPA, 2022)
Computational chemistry is a branch of chemistry which is the theoretical translated into computer programs to calculate the properties of molecules and their changes. This study analyzes the need of computational-based chemistry practicum in the Basic Chemistry course at the Chemistry Education Study Program at Samudra University. This study was done by survey technique. Aspects analyzed in this study include: module analysis through a review of the Basic Chemistry practicum module used by the Chemistry Education study program, needs analysis through students' perceptions that has been carried out, and literatures analysis through computational studies for Basic Chemistry that have been developed. Basic Chemistry practicum implemented in Chemistry Education is a verification practicum (conventional), and it is necessary to implement a practicum that gives more freedom to students in exploring. Basic chemistry practicum in Chemistry Education is also not based on computational, so it is necessary to develop basic chemistry practicum activities that provide computational problem solving